2018
DOI: 10.1016/j.ijnurstu.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A narrative meta-synthesis of how people with schizophrenia experience facilitators and barriers in using antipsychotic medication: Implications for healthcare professionals

Abstract: We advise professionals to adopt a person-centered approach to healthcare when encountering these patients and to transform the language used to describe patients from terms denoting compliance and adherence to terms denoting cooperation and alliance. Labeling patients as compliant or non-adherent may risk fortifying preconception of patients as static beings and obscure the patients' individual recovery process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 57 publications
4
24
0
Order By: Relevance
“…In addition to these findings a recent questionnaire study showed that both physicians and patients felt that patients were highly involved in the decision to switch to PP3M [22]. This is in line with previous research highlighting the importance of perceiving the source of information as reliable [29] and of having good relationships with health care professionals [18]. Most participants in our study had close relationships to both private and professional contacts (Table 1).…”
Section: Results Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition to these findings a recent questionnaire study showed that both physicians and patients felt that patients were highly involved in the decision to switch to PP3M [22]. This is in line with previous research highlighting the importance of perceiving the source of information as reliable [29] and of having good relationships with health care professionals [18]. Most participants in our study had close relationships to both private and professional contacts (Table 1).…”
Section: Results Discussionsupporting
confidence: 90%
“…Overall, research on the patients' perspectives on and experiences with antipsychotic medication is scarce [18]. Studies have shown that health care professionals prescribing PP3M are mostly satisfied with the efficacy and tolerability of the medications [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients included in our study had a documented diagnosis of schizophrenia. Treatment nonadherence rates in this population range from 26.5% to 68.8%, 17 which is significant because this increases the risk of suicide, psychotic relapse, and hospital admission. 18 Recent evidence suggests that LAI antipsychotics reduce the risk of rehospitalization in patients with schizophrenia compared to oral antipsychotics 19,20 ; therefore, these agents are often used at BUMCS in patients with a history of treatment nonadherence.…”
Section: Discussionmentioning
confidence: 98%
“…Knowledge of service user perspectives on the antipsychotic treatment of schizophrenia is limited . A number of studies have compared oral treatment with long‐acting injections (LAIs) .…”
Section: Purposementioning
confidence: 99%